Termination shock : a novel - Stephenson, Neal (William Morrow, an imprint of HarperCollinsPublishers, 2021)
A billionaire has an idea for reversing global warming, but will it work? And what will the consequences for the planet be? A disparate group of characters from around the globe fight to solve the problem of global warming, but some of their ideas may be worse than climate change itself.